Peran ajaran Teologi dalam Membangun karakter remaja kristen di Era Kontemporer - Habel Nain Samongilailai (Tri Tunggal: Jurnal Pendidikan Kristen dan Katolik, 2024)
This study examines the role of Christian theological teachings in forming adolescent characters in the contemporary era. The modern era, characterized by technological advances and rapid social changes, brings various challenges for adolescents regarding morality, spirituality, and decision-making. Through a descriptive qualitative approach, this research uses literature studies from various relevant sources to analyze how theological education can be a strong foundation in shaping character with integrity, strengthening faith, and developing moral resilience for Christian teenagers. The results show that the teachings of Christian theology not only play a role in building a personality based on Christian values but also help teenagers face the challenges of the contemporary era wisely and resolutely.